Development of Cybersecurity Competency and Professional Talent for Cyber Ummah - Ahmad, Rabiah; Abdul Rahman, Noraini; Zahrullayali, Zefrieda (Journal of Quranic Sciences and Research, 2023)
The world is facing with threats in digital transformation. Cyber threats become trending as reported by my countries. Developed countries like Britain, America, Europe and Japan already prepared countermeasures for various incidents on computer threats since Internet was introduced. They formulated and developed a successful model to produce computer security expert and highly skilled talent at various level diploma, bachelor and professional. University and College established academic program in computer and internet security at bachelor and postgraduate level. Industries at those countries introduced certification program in computer and internet security. Throughout our studies, limited initiatives related to talent development in combating computer security issues including cyber threats. Previous studies showed development of cybersecurity talent in Muslim countries is critical. Malaysia needs 20000 cybersecurity professional in 2025 and only achieved 2500 at present. This study presents our experience in developing cybersecurity competencies and professional talent for OIC-Country. We collaborated virtually with OIC-CERT (OIC Centre for Emergency and Response Team) in knowledge exchange, proposed appropriate competency model and participate in professional certification development. We presented the eight years active involvement with OIC-CERT activities. All initiatives established by OIC-CERT has produced outstanding impact to OIC Countries. One of the impactful initiatives known GlobalAce, it getting serious attention by many muslim countries. We also get benefit of other programs such as training for risks analysis, incident management and policy development. Our students be able to participate with Virtual Lecture on Combating Insider Threats, Cyber Threats Drill, and Security Audit. OIC-CERT also introduce the first Industry Journal in Cybersecurity known as OIC-CERT Journal of Cybersecurity.